2005
DOI: 10.1164/rccm.200407-863oc
|View full text |Cite
|
Sign up to set email alerts
|

Ethambutol Ocular Toxicity in Treatment Regimens for Mycobacterium avium Complex Lung Disease

Abstract: Ethambutol (EMB) is an important component of multidrug treatment regimens for Mycobacterium avium complex lung disease. Ocular toxicity is the most important potential EMB toxicity, especially in the elderly population with M. avium complex lung disease. Two hundred twenty-nine patients with M. avium complex lung disease, 55% women and 53% with nodular/bronchiectatic disease, received a mean of 16.1 +/- 10.8 months of multidrug therapy that included EMB. Fifty patients (22%) were known to have preexisting ocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 18 publications
2
51
0
1
Order By: Relevance
“…Multiple studies have shown the importance of ethambutol as a component of the treatment regimen for pulmonary MAC infection (130,132,139,345). The primary and most serious adverse effect associated with ethambutol is ocular toxicity.…”
Section: Treatment Of Nontuberculous Mycobacterial Infections Pulmonarymentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown the importance of ethambutol as a component of the treatment regimen for pulmonary MAC infection (130,132,139,345). The primary and most serious adverse effect associated with ethambutol is ocular toxicity.…”
Section: Treatment Of Nontuberculous Mycobacterial Infections Pulmonarymentioning
confidence: 99%
“…Patients on a high dose of drug (usually 25 mg/kg of body weight daily) present with blurred vision; decreased acuity; central scotomas; and, often, a loss of red-green color discrimination, and optic or retrobulbar neuritis may occur in one or both eyes. Sometimes, the central fiber of the optic nerve is affected, but more often, peripheral constriction of the visual fields occurs (139).…”
Section: Treatment Of Nontuberculous Mycobacterial Infections Pulmonarymentioning
confidence: 99%
“…5 The most serious potential adverse effect of Ethambutol toxicity is optic or retrobulbar neuritis, which may affect one or both eyes. 6 Pentoxifylline is a alkyl xanthine derivative 3,7-dimethyl 1-5 oxohexylaxtheme. 3 It was first synthesized in 1965.…”
Section: Discussionmentioning
confidence: 99%
“…However, MAC also represents a significant pathogen in certain populations, including the immune-compromised and particularly the elderly where non-tuberculous mycobacterial infection prevalence has risen to 30 of every 100,000 people older than 70 years of age, 11 or approximately 8350 persons based on 2010 Census data. Because many patients with MAC are also treated with ethambutol, and the medication's potential for visual toxicity, 12 we report a series of six patients who developed vision loss due to this treatment. These patients presented with bitemporal hemianopsias that mimic the clinical features for compressive optic neuropathy.…”
Section: Introductionmentioning
confidence: 99%